The moderating effects of nurses’ characteristics on the perceptions and practices of family-centered care for chronically ill children and their families in Saudi Arabia - Nada Alqarawi; Eman Alhalal; Ibrahim Alasqah (BMC Nursing)
Abstract Background/purpose Nurses play a vital role in providing effective family-centered care (FCC) to enhance the quality of healthcare for children with chronic illnesses and increase family satisfaction. This study aimed to investigate nurses' perceptions and practices of FCC for children with chronic illnesses, and how nursing characteristics influence this relationship. Method This multicenter cross-sectional study involved a convenience sample of 405 nurses, each with at least six months of experience caring for chronically ill children, infants, and toddlers in Saudi Arabia. An online survey was conducted between February 2023 and August 2023. A paired sample t-test of differences between nurses’ perceptions and practices of FCC among chronically ill children was performed. Correlations were carried out to test the relationships between nurses’ perceptions and practices of FCC and their sociodemographic factors, including age, gender, marital status, education level, and years of work experience, and attributes of nurses, including professional competence, interpersonal skills, job commitment, and knowing one’s self. Moderation analyses were conducted using the SPSS PROCESS macro version 4. Results Nurses’ FCC practice was significantly poorer than their perception. The moderation analysis highlighted that marital status (β = 0.122, p = .014), interpersonal skills (β = 0.131, p = .002), job commitment (β = 0.096, p = .024), and self-awareness (β = 0.127, p < .001) significantly strengthened the relationship between FCC perception and practice. Conclusions Nurses’ sociodemographic factors and personal attributes influenced the relationship between their perceptions of FCC and its implementation. Leaders should consider aspects such as marital status, interpersonal skills, job commitment, and self-awareness as these factors affect the strength of this relationship. Further research is needed to assess these impacts through longitudinal design and causal intervention studies to create a conceptual model of FCC for children with chronic illnesses.